2013
DOI: 10.1088/0253-6102/60/1/16
|View full text |Cite
|
Sign up to set email alerts
|

Working Mechanism of a BC 3 Nanotube Carbon Monoxide Gas Sensor

Abstract: Carbon and BN nanotubes have previously demonstrated extreme sensitivity to several molecules, but they cannot be used to detect highly toxic molecules of CO. In this work, we examine the possibility of a BC3 nanotube (BC3NT) as a potential gas sensor for CO detection by using density functional theory calculations. It is found that CO molecule can be absorbed on B and C atoms of BC3NT wall with adsorption energies in the range of −1.0 to −25.9 kcal/mol and it can donate finite charge to the tube. By comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The advantages of graphene-like semiconducting materials and their metal-decorated counterparts include nanodevice configuration that can have exceptional sensitivity and selectivity to few molecules, fast response in milliseconds to seconds, quick recovery, an ability to program the devices, and low cost using batch manufacturing. 27 Past work has shown that BC 3 nanotubes have the capability of detecting various hazardous gases such as CO. 28 C 3 N was also introduced as a platform for the sensing of NO 2 with good sensitivity and selectivity. 29 Moreover, it was reported that doping impurities such as Al and Si in BC 3 structures could improve the adsorption of molecules like formaldehyde (H 2 CO).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The advantages of graphene-like semiconducting materials and their metal-decorated counterparts include nanodevice configuration that can have exceptional sensitivity and selectivity to few molecules, fast response in milliseconds to seconds, quick recovery, an ability to program the devices, and low cost using batch manufacturing. 27 Past work has shown that BC 3 nanotubes have the capability of detecting various hazardous gases such as CO. 28 C 3 N was also introduced as a platform for the sensing of NO 2 with good sensitivity and selectivity. 29 Moreover, it was reported that doping impurities such as Al and Si in BC 3 structures could improve the adsorption of molecules like formaldehyde (H 2 CO).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The capability of BC 3 as a gas sensor has been evaluated in the literature [50][51][52][53]. Beheshtian et. al.…”
Section: Introductionmentioning
confidence: 99%
“…[18] It has been shown that an increasei ng raphene charge-carrier concentration induced by adsorbed gas molecules can be used to make highly sensitive sensors, which even show potential to detect individual molecules. Based on earlier investigations, [13,[18][19][20] it is also interesting to exploit the possibility of h-BC 3 serving as ag as sensor. Here, we have performed first principles calculations for CO, CO 2 ,N O, NO 2 ,a nd NH 3 molecules adsorbed onto BC 3 sheets.F or ac lean and safe environment,i ti sn ecessary to understand the interaction of these gases with BC 3 surfaces.…”
Section: Introductionmentioning
confidence: 99%